Rho GTPases as pathogen targets: Focus on curable sexually transmitted infections - Quintero, Cristian Andres (2015)
Pathogens have evolved highly specialized mechanisms to infect hosts. Several microorganisms modulate the eukaryotic cell surface to facilitate their engulfment. Once internalized, they hijack the molecular machinery of the infected cell for their own benefit. At different stages of phagocytosis, particularly during invasion, certain pathogens manipulate pathways governed by small GTPases. In this review, we focus on the role of Rho proteins on curable, sexually transmitted infections caused by Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis and Treponema pallidum. Despite the high, worldwide frequencies of these sexually-transmitted diseases, very little is known about the strategies developed by these microorganisms to usurp key eukaryotic proteins that control intracellular signaling and actin dynamics. Improved knowledge of these molecular mechanisms will contribute to the elucidation of how these clinically important pathogens manipulate intracellular processes and parasitize their hosts.